Factors associated with COVID-19 severity and mortality among Hispanic patients living on the USA–Mexico border. (29th January 2021) - Cervantes, Jorge; Sureen, Amit; Galura, Gian; Dodoo, Christopher; Dwivedi, Alok Kumar; Bashashati, Mohammad; Zuckerman, Marc; Meza, Armando
Abstract : COVID-19 has ravaged the medical, social, and financial landscape across the world, and the USA–Mexico border is no exception. Although some risk factors for COVID-19 severity and mortality have already been identified in various ethnic cohorts, there remains a paucity of data among Hispanics, particularly those living on borders. Ethnic disparities in COVID-19 outcomes in Hispanic and black populations have been reported. We sought to identify the clinical presentation, treatment, laboratory, and imaging characteristics of 82 Hispanic patients in a county hospital and describe the factors associated with rates of hospitalization, intensive care unit (ICU) admission, and mortality. The most common comorbidities were hypertension (48.8%) and diabetes mellitus (DM) (39%), both found to be associated with hospitalization and mortality, while only DM was associated with increased rate of ICU admission. Multivariable analysis showed that individuals with fever, low oxygen saturation (SpO2 ), nasal congestion, shortness of breath, and DM had an increased risk of hospitalization. Individuals with fever, decreased levels of SpO2, and advanced age were found to be associated with an increased risk of death. The most common cause of death was respiratory failure (28.9%), followed by shock (17.8%) and acute kidney injury (15.6%). Our findings are critical to developing strategies and identifying at-risk individuals in a Hispanic population living on borders. Research aiming to identify key evidence‐based prognostic factors in our patient population will help inform our healthcare providers so that best interventions can be implemented to improve the outcomes of patients with COVID-19.